Structure–Function Relationship between Flicker-Defined Form Perimetry and Spectral-Domain Optical Coherence Tomography in Glaucoma Suspects. (4th March 2017) - Reznicek, Lukas; Muth, Daniel; Vogel, Michaela; Hirneiß, Christoph
ABSTRACT: Purpose : To evaluate the relationship between functional parameters of repeated flicker-defined form perimetry (FDF) and structural parameters of spectral-domain optical coherence tomography (SD-OCT) in glaucoma suspects with normal findings in achromatic standard automated perimetry (SAP). Methods : Patients with optic nerve heads (ONH) clinically suspicious for glaucoma and normal SAP findings were enrolled in this prospective study. Each participant underwent visual field (VF) testing with FDF perimetry, using the Heidelberg Edge Perimeter (HEP, Heidelberg Engineering, Heidelberg, Germany) at two consecutive visits. Peripapillary RNFL thickness was obtained by SD-OCT (Spectralis, Heidelberg Engineering, Heidelberg, Germany). Correlations and regression analyses of global and sectoral peripapillary RNFL thickness with corresponding global and regional VF sensitivities were investigated. Results : A consecutive series of 65 study eyes of 36 patients were prospectively included. The second FDF test (HEP II) was used for analysis. Cluster-point based suspicious VF defects were found in 34 eyes (52%). Significant correlations were observed between mean global MD (PSD) of HEP II and SD-OCT-based global peripapillary RNFL thickness ( r = 0.380, p = 0.003 for MD and r = –0.516, p < 0.001 for PSD) and RNFL classification scores ( R 2 = 0.157, p = 0.002 for MD and R 2 = 0.172, p = 0.001 for PSD). Correlations between mean global MD and PSD of HEP II and sectoral peripapillary RNFL thickness and classification scores showed highest correlations between function and structure for the temporal superior and temporal inferior sectors whereas sectoral MD and PSD correlated weaker with sectoral RNFL thickness. Correlations between linear RNFL values and untransformed logarithmic MD values for each segment were less significant than correlations between logarithmic MD values and RNFL thickness. Conclusions : In glaucoma suspects with normal SAP, global and sectoral peripapillary RNFL thickness is correlated with sensitivity and VF defects in FDF perimetry.